Prevalence and sources of stress among medical students in Universiti Sains Malaysia (USM) - Yusoff, Muhamad Saiful Bahri (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Background: Being in medical school has always been regarded as highly stressful. Excessive physical and mental health problems. Persistent stress can impair students' acsdemic achieomnent and personal or professional development. The aim of this study is to explore the nature of stnss among medical students by determining the prevalence, sourcea and pattem of stress and the fildors affecting it. Methods: We chose a cross-sectional study design utilizing validated questionnaires, the 12 items General Health Questionnaire (GHQ-12) and Medical Student Stressor Questionnaire (MSSQ), to evaluate stress levels and stressors. School and ethical committee clearance were obtained prior to tbe study. Data were analysed using SPSS version 12 • Results: Of the medical students who were administered the questionnaire, 761 (72%) respondents participated in this study. The prevalence of stress among the medical students was 29.6%. The top 10 stressors were aeademic-related. Prevalence of stress for the first, second, third, fourth and fifth year students was 26.3%, 36.5 %, 31.4%, 35·3% and 21.9%, respectively. Year of study was the only significant factor affecting stress among medical students (P-value < o.os) . Conclusions: The prevalence of stress among medical students in USM is high. Academic· related problems were the ml\ior stressor among medical students. Year of study was the factor most siguific:antly associated with medical students' stress. There was a bimodal pattern of the stress level thruughout the year of study •